THE EFFECT OF STRESS ON SMOOTHNESS OF BREAST MILK PRODUCTION IN POSTPARTUM MOTHER IN DELIMA (PARTURITION) ROOM OF SAYANG REGIONAL GENERAL HOSPITAL CIANJUR - Rahayu, Dedeh Sri; Disania Fatmawati; Aan Somana (STIKes Budi Luhur Cimahi, 2025)
According to WHO data, the global average rate of exclusive breastfeeding in 2016 was approximately 38%. Many mothers face challenges during breastfeeding, with one common issue being disrupted milk flow. One contributing factor to this problem is maternal stress. Sayang Regional General Hospital in Cianjur is a maternal and child healthcare provider that handles around 5,679 childbirths annually. This study aimed to examine the effect of stress on the smoothness of breast milk production among postpartum mothers in the Delima (Parturition) Room at Sayang Regional General Hospital, Cianjur, in 2019. This research employed a descriptive correlational design with a cross-sectional approach. The study population consisted of 176 postpartum mothers, and 64 were selected using purposive sampling. Data were collected using the Depression Anxiety Stress Scales (DASS-42), structured questionnaires, and interviews to assess the smoothness of breast milk production. Univariate analysis was conducted using frequency distribution, while bivariate analysis used the Chi-Square test. Results showed that 29.7% of mothers experienced stress, and 65.6% had disrupted breast milk flow. The Chi-Square test revealed a significant relationship between stress and breast milk production smoothness, with a p-value of 0.001 (p < 0.05). These findings suggest that maternal stress negatively affects the smoothness of breast milk production. It is recommended that nurses and midwives provide additional support to breastfeeding mothers by offering emotional encouragement, teaching correct breastfeeding techniques, and avoiding rigid breastfeeding schedules to help reduce stress and improve breastfeeding outcomes. Keywords : Smoothness of breast milk flow, Stress, Postpartum